Association of food security with cardiometabolic health during young adulthood: cross-sectional comparison of American Indian adults with other racial/ethnic groups - Cassandra J Nikolaus; Anna Zamora-Kapoor; Luciana E Hebert; Ka'imi Sinclair (BMJ Open)
Objectives Our aim was to assess the cross-sectional associations between food insecurity and cardiometabolic health indicators in American Indian young adults compared with non-Hispanic white, black, Asian or Pacific Islander and Hispanic young adults.Design Data from the fourth wave of the National Longitudinal Study of Adolescent to Adult Health (Add Health) were used. Variables included a self-assessed measure of risk of food insecurity, indicators of cardiometabolic health (body mass index, haemoglobin A1c, blood pressure) and sociodemographic characteristics. Multivariable regression models were used to assess the association of risk of food insecurity with cardiometabolic health, while controlling for sociodemographic variables. All analyses were weighted and accounted for the complex survey design.Participants The analytical sample of n=12 799 included mostly non-Hispanic white respondents (n=7900), followed by n=2666 black, n=442 American Indian, n=848 Asian or Pacific Islander and n=943 Hispanic.Results Risk of food insecurity was more common among respondents who were female, Black, American Indian, had lower educational attainment, and were classified as having obesity or diabetes. In unadjusted models, risk of food insecurity was significantly associated with greater odds of obesity (OR=1.39; 95% CI 1.20 to 1.60) and diabetes (OR=1.61; 95% CI 1.23 to 2.11). After adjusting for sociodemographic factors (age, sex, education, income, household size, tobacco smoking, alcohol intake and race/ethnicity), only the association between risk of food insecurity and obesity remained (OR=1.19; 95% CI 1.03 to 1.38). Relationships among risk of food insecurity, sociodemographic characteristics and diabetes varied across models stratified by race and ethnicity.Conclusions Results suggest that elevated risk of food insecurity is present in young American Indian adults, but its relationship with cardiometabolic health is unclear. Future work should capitalise on longitudinal data and the US Department of Agriculture’s Food Security Survey Modules.